2015
DOI: 10.1039/c4tx00145a
|View full text |Cite
|
Sign up to set email alerts
|

The Zishen Yutai pill shows no reproductive toxicity on embryo-fetal development in rats and rabbits

Abstract: Objective: the Zishen Yutai pill (ZYP) is one of the most commonly used Chinese medicines to prevent miscarriage. However, its safety during pregnancy remains ill-defined. In this study, we aimed to investigate the potential reproductive toxicity of ZYP on embryo-fetal development. Methods: various doses of ZYP were given to pregnant rats (6, 12 and 24 g kg −1 d −1 ; i.e. 24×, 48× and 96× clinical doses) and rabbits (1.5, 3.0 and 6.0 g kg −1 d −1 ; i.e. 6×, 12× and 24× clinical doses) by intragastric administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Herein, we begin to address this issue for ZYP in three reproductive toxicology studies in succession, including its effects on fertility and early embryonic development in rats (segment I), embryo-fetal development in rats and rabbits (segment II), and prenatal and postnatal development in rats (segment III). In the embryo-fetal development study, we found that only mild maternal toxicities of ZYP were detected in rats at the dose of 24 g/kg/d and were limited to decreased extra-uterine weight gain and food intake, and there was no reproductive toxicology in rabbits even at the maximum administration dose [11]. The present preclinical study further reports the effects of ZYP on fertility and early embryonic development in male and female rats, which provides needed preclinical safety evidence to support its clinical usage.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we begin to address this issue for ZYP in three reproductive toxicology studies in succession, including its effects on fertility and early embryonic development in rats (segment I), embryo-fetal development in rats and rabbits (segment II), and prenatal and postnatal development in rats (segment III). In the embryo-fetal development study, we found that only mild maternal toxicities of ZYP were detected in rats at the dose of 24 g/kg/d and were limited to decreased extra-uterine weight gain and food intake, and there was no reproductive toxicology in rabbits even at the maximum administration dose [11]. The present preclinical study further reports the effects of ZYP on fertility and early embryonic development in male and female rats, which provides needed preclinical safety evidence to support its clinical usage.…”
Section: Introductionmentioning
confidence: 99%